2009
DOI: 10.1016/s1002-0160(08)60078-8
|View full text |Cite
|
Sign up to set email alerts
|

Soil Drainage as an Active Agent of Recent Soil Evolution: A Review

Abstract: While research on pedogenesis mainly focuses on the long-term soil formation and most often neglects recent soil evolution in response to human practices or climate changes, this article reviews the impact of artificial subsurface drainage on soil evolution. Artificial drainage is considered as an example of the impact of recent changes in water fluxes on soil evolution over time scales of decades to a century. Results from various classical studies on artificial drainage including hydrological and environment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(15 citation statements)
references
References 62 publications
0
12
0
3
Order By: Relevance
“…/ jun. 2016 Além dos aspectos relacionados à deposição de sedimentos, a concentração maior de nutrientes nas parcelas iniciais das transecções B e C pode ser resultado da drenagem deficiente observada nesses locais, que reduz as perdas de bases pelo processo de lixiviação e retarda a decomposição da matéria orgânica (MONTAGNE et al, 2009). Observa-se, na figura 2, a tendência apresentada pelos teores de P, K, Ca e Mg nas transecções B e C, demonstrando a existência de um gradiente edáfico, com redução nos teores de macronutrientes do solo à medida que as subunidades se afastam da zona de deposição de deflúvios e de drenagem deficiente.…”
Section: Similaridade Das Unidades Amostraisunclassified
“…/ jun. 2016 Além dos aspectos relacionados à deposição de sedimentos, a concentração maior de nutrientes nas parcelas iniciais das transecções B e C pode ser resultado da drenagem deficiente observada nesses locais, que reduz as perdas de bases pelo processo de lixiviação e retarda a decomposição da matéria orgânica (MONTAGNE et al, 2009). Observa-se, na figura 2, a tendência apresentada pelos teores de P, K, Ca e Mg nas transecções B e C, demonstrando a existência de um gradiente edáfico, com redução nos teores de macronutrientes do solo à medida que as subunidades se afastam da zona de deposição de deflúvios e de drenagem deficiente.…”
Section: Similaridade Das Unidades Amostraisunclassified
“…The clear increase of subsurface drainflow immediately after the drainage improvement (Fig. 2) was mainly affected by the good permeability of the backfill material (gravel, topsoil/wood chips) of the drain trench allowing the water infiltrate and drain quickly from surface and topsoil to deeper layers as discussed in Turtola and Paajanen (1995) and Montagne et al (2009). We can also presume that the ploughing of the soil (normal to drain pipelines) enhanced the subsurface drainflow by increasing the temporal water storage capacity of wet soil during rainy and snow melting periods, and by conducting the topsoil layer runoff (in 0-20 cm) towards drain trench.…”
Section: Resultsmentioning
confidence: 96%
“…These results are in good agreement with macroscopic observations. Montagne et al (2009) showed that by removing the excess of water, agricultural drainage induces two gradients of water fluxes and of redox conditions between the mid-drain position and the immediate vicinity of the drain. These gradients have not induced a marked soil differentiation between position 210 and position 400.…”
Section: Nature Of the Impact Of Agricultural Drainage On Soil Changesmentioning
confidence: 99%